Respiratory virus-induced bacterial dysregulation in pediatric airway tissue and the dual actions of Echinacea in reducing complications - Vimalanathan, Selvarani; Sreya, Mahfuza; Nandanavanam, Ranganayaki; Schoop, Roland; Gancitano, Giuseppe; Saberi, Saba; Malikovskaia, Anna; Hudson, James (Frontiers in Pharmacology, 2025)
IntroductionRespiratory tract infections (RTIs) contribute to pediatric morbidity and are often complicated by viral-bacterial superinfections, which exacerbate disease severity and increase antibiotic use. This study examined viral-induced bacterial adhesion in an ex vivo pediatric airway model and the therapeutic potential of Echinacea purpurea extract.MethodsEpiAirway tissue from a 6-year-old boy was infected with respiratory syncytial virus (RSV), human parainfluenza virus type 3 (HPIV3), or rhinovirus 14 (RV14). Adhesion of Haemophilus influenzae type b (Hib) and Streptococcus pneumoniae (S. pneumoniae) was assessed alongside the expression of platelet-activating factor receptor (PAFr), intercellular adhesion molecule-1 (ICAM-1), and carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM-1). Echinaforce® (EF extract) was tested for its effect on bacterial dysregulation.ResultsRSV and HPIV3 increased bacterial adhesion by upregulating PAFr, ICAM-1, and CEACAM-1. Hib adhered primarily via ICAM-1, while S. pneumoniae favored PAFr. RV14 strongly induced CEACAM-1 but did not cause significant bacterial dysregulation. EF significantly reduced virus-induced receptor overexpression, resulting in inhibition of bacterial adhesion and biofilm-like formation.ConclusionOur findings provide a mechanistic explanation for the observed effects of E. purpurea in reducing RTI complications and the need for antibiotic prescriptions in clinical settings.